Intelligent supervisory control for microelectronics fabrication - Ling, Sze Ling. (2012)
In this project, we will focus on the diffusion process, which is one of the processes under microelectronics fabrication process. In the past, the control process is controlled by an engineer, based solely on his experiences and collected data. Hence, the accuracy of the output thickness of the wafer is an issue of the process.